2013
DOI: 10.1208/s12248-013-9473-7
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol Suppresses T0901317-Induced Hepatic Fat Accumulation in Mice

Abstract: Abstract. Liver X receptor (LXR) has been identified as a potential target for treatment of atherosclerosis and diabetes. Activation of LXR, however, is associated with increased lipogenesis and fat accumulation in the liver. The objective of the current study was to examine the effect of resveratrol on LXR activator-induced fat accumulation in liver using mice as an animal model. Three groups of C57BL/6 mice were studied. Animals in group 1 were treated with T0901317, a potent activator of LXR in mice. Animal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
16
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 36 publications
1
16
0
Order By: Relevance
“…The procedure for quantitative determination of liver triglyceride has been previously described [20]. Liver samples (200-400 mg) were homogenized in a mixture of chloroform and methanol (2:1, volume ratio), and thereafter incubated overnight at 4°C.…”
Section: Methodsmentioning
confidence: 99%
“…The procedure for quantitative determination of liver triglyceride has been previously described [20]. Liver samples (200-400 mg) were homogenized in a mixture of chloroform and methanol (2:1, volume ratio), and thereafter incubated overnight at 4°C.…”
Section: Methodsmentioning
confidence: 99%
“…490 Baur et al [19] investigated resveratrol supplementation at a dose terol accumulation [35,[69][70][71][72][73][74], hepatic triglycerides [35,47,66,69,70,72,527 75-79] and liver weight [19,48,70,73,76,77]. Also, several other im-528 provements in liver fat content and anatomy were reported in rodents 529 after resveratrol supplementation [19,[48][49][50]67,[69][70][71][72]74,[76][77][78][79][80][81][82]. For To date, only four clinical trials have been performed investigating 536 effects of resveratrol on liver fat accumulation.…”
mentioning
confidence: 99%
“…32 The agents inhibiting LXR-α and LXR-α-dependent lipogenesis do not enhance RCT. 33,34 A few studies have reported that activation of LXR can regulate RCT or atherosclerosis in an ABCA1-or macrophageindependent manner. T0901317 increases RCT to a similar degree in wild-type mice injected with radiolabeled wild-type macrophages or LXR-deleted macrophages, whereas it had little effect on LXR-deficient mice injected with wild-type macrophages.…”
mentioning
confidence: 99%